Sistem Informasi Pelaporan Monografi pada Kantor Kecamatan Ilir Timur III Palembang - Siregar, Kipen Sandri; Heriati, Agustina (Jurnal Sistem Informasi dan Teknik Informatika (JAFOTIK), 2023)
The web-based information system used in the monograph reporting process is applied information technology in the field of management. The use of a monograph information system aims to make it easier to manage monograph reports in an integrated, transparent, and real-time manner. This research aims to provide a web-based monographic information system in Ilir Timur III District, Palembang, to provide always up-to-date government reports. The method for designing this system uses a waterfall approach with three stages, namely collecting software requirements, and designing and evaluating the proposed system. This prototype design provides a web-based monographic information system that can manage data on underground water, street lighting, and the presence of integrated advertising, as well as making it easier to create and present reports.